Mapping wheelchair functions and their associated functional elements for stair climbing accessibility: a systematic review. - Verma, Abhishek; Shrivastava, Siddhant; Ramkumar, Janakarajan (Disability & Rehabilitation: Assistive Technology, 2024)
Wheelchair (WC) design elements are subjected to the accessibility and assistive needs of a person with locomotor disability. In order to pursue a holistic design for a stairclimbing WC, there is a need for literature review on WC functions reported for both stair climbing and plane surface movement. A total of 112 Research articles are reviewed for the purpose of extracting the relationship between WC design elements and the functions associated with them. Stairclimbing technologies are reviewed for their technological assessment in terms of functional elements associated with stairclimbing. Cross-functional mapping between functional elements and their dominant function is performed. Heat map for primary user needs and associated design elements is generated from cross mapping. A design gap for user's functional needs is indicated from the review of literature on prototypes and products of WC. The literature in stairclimbing technology is primarily focussed on stair climbing capability and not on the other functional needs, such as safety, ride comfort, seat comfort, manoeuvrability, etc. For attaining the goal of an effective rehabilitation, it is important to design and develop an assistive technology that can provide maximum accessibility and functioning for a person with disability. In case of locomotor disability, wheelchair (WC) is the most empowering tool that can assist people in both accessibility and activities of daily living. This review of literature was conducted to draw out the functions fulfilled by a WC, such as safety, comfort, propulsion for its users and the associated WC elements like seat, wheels, backrest, etc., that are required to fulfil those functions. WC being the most important technological intervention in the life of a person who cannot walk should be designed with the highest level of empathy. Therefore, each and every aspect of the user's physical and emotional needs should be catered up to the limits of engineering design. The research on stair climbing technologies has also grown exponentially, fuelled by technological growth in engineering mechanisms, ambient awareness sensors, actuators, etc. The review attempts to envelop such technologies and consolidate them on the basis of their capabilities and efficacies. The virtue of stair climbing has been realized through some novel and innovative mechanisms reviewed in this article that can be integrated with the research in field of functional elements required to carry out primary functions of a disabled person, such as safety, comfort, intuitiveness, etc. This review can help in coupling both of them in a more rational way where a designer who is designing the technology is more empathetic towards the design for accessibility. It can also help user in becoming more confident towards adapting a new assistive technology.